(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
The practice of intestate succession has undergone significant evolution, with recent developments highlighting concerns about human rights and the importance of respecting an egalitarian society. The practice in Nigeria, especially with the application of customary law, is shrouded in the discrimination of rights; in all of these, women are mostly affected, considering their copious vulnerabilities. It is in light of these concerns that Nigeria needs to adopt and implement international best standards. Why should Nigeria adopt and implement these international best standards? What are the potential premiums accruing to the implementation of international treaties centered on promoting minority rights, like those affecting women and children? These are some of the key questions answered in this article. The methodology used for this research is doctrinal. It relied on primary and secondary sources such as legal texts, judicial decisions, journals, the internet, international treaties, and conventions to analyze the interplay between domestic and international legal frameworks in addressing the rights of women and children in inheritance matters. The findings reveal that, despite constitutional guarantees of equality, Nigerian customary and religious practices often undermine women’s and female children’s rights to inheritance. Judicial interventions have provided some relief by invalidating discriminatory customs, but such relief remains inconsistent and limited. The research further demonstrates that international treaties—such as the Protocol to the African Charter on Human and Peoples’ Rights on the Rights of Women in Africa (Maputo Protocol), the African Charter, Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), and the Universal Declaration of Human Rights (UDHR) offer normative frameworks that, once domesticated, can serve as binding legal instruments to protect women’s inheritance rights and harmonize Nigeria’s fragmented legal order. The article concludes that effective domestication and implementation of key international treaties, particularly CEDAW and the African Charter, will empower courts to expunge discriminatory customary practices and ensure that domestic succession laws align with Nigeria’s international human rights obligations. The study recommends enhanced judicial training, legislative reforms, and public sensitization to facilitate the consistent protection of women’s rights and promote fairness and equality in intestate succession.